2014
DOI: 10.1038/mi.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum enhances inflammation and decreases mucosal healing in experimental colitis in mice

Abstract: The increasing incidence of inflammatory bowel diseases (IBDs) in developing countries has highlighted the critical role of environmental pollutants as causative factors in their pathophysiology. Despite its ubiquity and immune toxicity, the impact of aluminum in the gut is not known. This study aimed to evaluate the effects of environmentally relevant intoxication with aluminum in murine models of colitis and to explore the underlying mechanisms. Oral administration of aluminum worsened intestinal inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 48 publications
3
75
0
Order By: Relevance
“…The principal exposure route to Al for humans is through food, water and beverages [2]. The mean levels of Al exposure via this route range from 0.2 to 1.5 mg/kg of body weight (bw) weekly in Europe and 1.3 mg/kg·bw/week for adults and 3.3 mg/kg·bw/week for children in China [3].…”
Section: Introductionmentioning
confidence: 99%
“…The principal exposure route to Al for humans is through food, water and beverages [2]. The mean levels of Al exposure via this route range from 0.2 to 1.5 mg/kg of body weight (bw) weekly in Europe and 1.3 mg/kg·bw/week for adults and 3.3 mg/kg·bw/week for children in China [3].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Mn present in the samples here evaluated, concentrations were above that recommended for daily consumption [38,39,54] (Table 3). In comparison to the study realized by Okem et al [51] evaluating commercial herbs in South Africa, the Mn concentrations in this present study, were higher than those reported.…”
Section: Resultsmentioning
confidence: 91%
“…These data are similar the three highest concentrations identified in the dried samples currently analyzed. Although iron is an essential metal for plants and animals, elevated levels are not beneficial and considered air pollution [54], and it has been reported as accumulation metal in plants evaluated in Macedonia (515 mg.kg -1 ). Considering Mn, Maharia et al [56], registered in herbal products concentration of 601.0 mg kg −1 .…”
Section: Resultsmentioning
confidence: 98%
“…The impact of Aluminum (Al) on neural tissues is well known [10]. It has been implicated in many aging related changes as well as in neurodegenerative diseases.…”
Section: Modeling Stages Of Alzheimer's Disease In Ratsmentioning
confidence: 99%